2020
DOI: 10.1111/joor.12966
|View full text |Cite
|
Sign up to set email alerts
|

Symptom severity in burning mouth syndrome associates with psychological factors

Abstract: Burning mouth syndrome (BMS) patients are psychologically distressed, but whether this associates with symptom severity is unclear. The aim was to investigate the association of psychological factors with pain intensity and interference in BMS. Fifty‐two women (mean age 63.1, SD 10.9) with BMS participated. Pain intensity and interference data were collected using 2‐week pain diaries. Psychological factors were evaluated using Depression Scale (DEPS), Pain Anxiety Symptom Scale (PASS) and Pain Vigilance and Aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 47 publications
1
31
1
Order By: Relevance
“…Pain and psychological distress are strictly interconnected because patients suffering chronic pain are at risk of developing long‐lasting anxiety and depression, just as patients with mood disorders can report somatic pain (Blackburn‐Munro & Blackburn‐Munro, 2001; Chou, 2007). In previous studies, a high prevalence of anxiety, depression, and sleep disturbance (Adamo et al., 2018; Galli et al, 2017; Schiavone et al, 2012) in patients with BMS has been reported; similarly, Forssel et al have evidenced, in a recent article, that patients with a higher intensity of pain show an increased level of depression and anxiety symptoms (Forssel, Teerijoki‐Oksa, Puukka, & Estlander, 2020).…”
Section: Introductionmentioning
confidence: 81%
“…Pain and psychological distress are strictly interconnected because patients suffering chronic pain are at risk of developing long‐lasting anxiety and depression, just as patients with mood disorders can report somatic pain (Blackburn‐Munro & Blackburn‐Munro, 2001; Chou, 2007). In previous studies, a high prevalence of anxiety, depression, and sleep disturbance (Adamo et al., 2018; Galli et al, 2017; Schiavone et al, 2012) in patients with BMS has been reported; similarly, Forssel et al have evidenced, in a recent article, that patients with a higher intensity of pain show an increased level of depression and anxiety symptoms (Forssel, Teerijoki‐Oksa, Puukka, & Estlander, 2020).…”
Section: Introductionmentioning
confidence: 81%
“…The referred symptoms are multifarious including burning, xerostomia, sialorrhea, taste disturbances, itching, and coating tongue, and the most common affected sites are tongue, palate, gingivae, and lower lips 20 . While the association with sleep disturbances and psychological disorders is widely documented, 21 few data are presented on other somatic comorbidities. Moisset et al reported rare co‐occurrence of pain and BMS, often represented by headache, TMDs, atypical facial pain, trigeminal neuralgia, post‐herpetic facial pain, back pain, fibromyalgia, joint pain, abdominal pain, rectal pain, or vulvodynia 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Partial correlations (parametric and non‐parametric) controlling for pain severity were subsequently administered for significant bivariate correlations. To control for possible type I errors due to multiple tests of associations, the false discovery rate approach was applied to the set of correlations with control set to 5% 21 . Associations between questionnaire scale scores and demographic and clinical characteristics measures were explored using Pearson correlation coefficients (and Spearman's rho ) and independent groups t tests.…”
Section: Methodsmentioning
confidence: 99%
“…It is surprising then that despite the long‐held and ongoing interest in the relationship between affective dysfunction and BMS, 8,9,18 few studies with BMS patients have examined beliefs about personal capacities to cope with or adapt to chronic pain and their association with patient mood and symptom management. A small number of studies have reported that pain‐specific psychological variables including catastrophising, pain anxiety and pain hypervigilance influence pain severity, pain interference and oral HRQoL in BMS, 4,19‐21 suggesting these are important components of patients’ pain experience. However, the association of catastrophising with BMS patient levels of anxiety or depressive symptoms is not clear, and as recently noted by Forssell and colleagues, 21 little is known about the resilience aspects of pain in BMS patients, which include pain self‐efficacy and chronic pain acceptance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation